School Literacy Movements to Build Character Students in the 21st-Century Education - Bambang Wijayadikusumah (International Conference on Elementary Education, 2023)
Literacy in Indonesia is still low. Educational leaders have launched school literacy movement programs literacy. The school literacy movements increases reading interest and read culture in a school environment to create a lifetime of literates of sterling character and competence in the face of 21st-century education. The school literacy movement as an effort to build core character values combined with the 21st-century education competence through the breeding, learning, and development stages. The study aims to review and explain the concept of the school literacy movement in building student character values in elementary school. The method used in this study is literature review (SLR). The results of this study are conceptually demonstrated by the school's literacy movement to be an integration of major religious, nationalist, independent, cooperative, integrity with the competence of creativity, communication competence, critical thinking competence, and collaborative competence to prepare students above all for 21st-century education.